2018
DOI: 10.1186/s12935-018-0711-z
|View full text |Cite
|
Sign up to set email alerts
|

Speckle-type POZ protein functions as a tumor suppressor in non-small cell lung cancer due to DNA methylation

Abstract: BackgroundTumor suppressor epigenetic silencing plays an important role in non-small cell lung cancer (NSCLC) development and progression. Previously, the expression of speckle-type POZ protein (SPOP) has been found to be significantly inhibited in NSCLC. Our research aimed to investigate the molecular mechanisms, clinical significance and epigenetic alteration of SPOP in NSCLC.Materials and methodsBisulfite sequencing PCR and methylation-specific PCR were performed to test gene methylation. Chromatin immunopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In detail, the loss-of-function mutations of SPOP could prevent ubiquitination-mediated PD-L1 degradation, demonstrating that patients with prostate cancer had a worse prognosis and therapy effect through increasing PD-L1 levels and decreasing tumor-infiltrating lymphocytes [ 5 ]. Meanwhile, except for the loss-of-function mutations of SPOP, the hypermethylation of SPOP also led to a decrease in SPOP mRNA and protein levels, suggesting that SPOP was regulated by epigenetic pathways [ 36 , 37 ]. Notably, SPOP not only can be functionalized as a tumor suppressor by targeting androgen receptor for degradation, but also as an oncoprotein in renal cancer, resulting in activation of androgen receptor driven pathways [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In detail, the loss-of-function mutations of SPOP could prevent ubiquitination-mediated PD-L1 degradation, demonstrating that patients with prostate cancer had a worse prognosis and therapy effect through increasing PD-L1 levels and decreasing tumor-infiltrating lymphocytes [ 5 ]. Meanwhile, except for the loss-of-function mutations of SPOP, the hypermethylation of SPOP also led to a decrease in SPOP mRNA and protein levels, suggesting that SPOP was regulated by epigenetic pathways [ 36 , 37 ]. Notably, SPOP not only can be functionalized as a tumor suppressor by targeting androgen receptor for degradation, but also as an oncoprotein in renal cancer, resulting in activation of androgen receptor driven pathways [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…[19] Hypermethylation of CpG island in the promoter region has been identified as an important cause for downregulation of gene expression. [20,21] So, the phenomenon that hypermethylation of SLC16A12 suggests that SLC16A12 might be a critical tumor suppressor. However, no exact researches on the expression and mechanism of SLC16A12 in tumors were available up to now.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Similarly, in NSCLC, hypermethylation of CpG islands of SPOP prevented it from binding to another transcription factor, C/EBPα, and promoted invasion, migration, proliferation in vitro and tumor growth in vivo. [6] SPOP, as a vital suppressor of oncogene, has drawn wide attentions for implicating a potential prognostic value and therapeutic target for future medication. It was reported that decreased expression of SPOP consistently occurred in glioma patients, which was positively correlated with advanced tumor grade and worse survival.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mounting evidence suggested that downregulation of SPOP expression extensively occurs in various tumor tissues due to mutations and DNA methylations. [6,7] Ju et al demonstrated that SPOP exhibits a tumor repressor role via targeting cyclin E1 and promotes the cell proliferation, migration, and tumor formation. [8] Similarly, Groner et al reported that SPOP, but not its mutants, promotes the ubiquitination and degradation of TRIM24 and hereby inhibits tumorigenesis and development of tumor.…”
Section: Introductionmentioning
confidence: 99%